Sanksi Pelanggaran Kode Etik Advokat - Ary Darma Prastio; M. Irkham; Fauziah Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to find out what forms of violations are often committed by an Advocate. Violation becomes a problem if an advocate violates the law, because an advocate has a code of ethics that regulates it in proceedings before a court or helps resolve a case. Advocates must comply with a code of ethics and if they violate it, an advocate will receive sanctions. There are advocates who commit acts of violating the law, such as abusing their duties in defending clients so that the cases they handle win in court. Keywords: Violation, Code of Ethics, Sanctions